Screening of promising maize genotypes against maize weevil (Sitophilus zeamais Motschulky) in storage condition - Paneru, Ram B; Thapa, Resham B (Journal of Maize Research and Development, 2018)
The maize weevil (Sitophilus zeamais Motschulsky) is a serious pest of economic importance in stored grains. It causes major damage to stored maize grain thereby reducing its weight, quality and germination. An experiment was conducted in randomized complete block design (RCBD) with 3 replications to screen 32 maize genotypes against maize weevil in no-choice and free-choice conditions at Entomology Division, Khumaltar, Lalitpur (Room temperature: Maximum 24-32°C and Minimum 18-27°C). The findings showed that the maize genotypes had different response to maize weevil damage ranging from susceptible to tolerance. The genotypes Manakamana-3, Lumle White POP Corn and Ganesh-2 showed their tolerance to S. zeamais as evidenced by lower number of weevil emerged/attracted, lower amount of grain debris release and lower proportion of bored grains, while the genotype ZM-627 was the most susceptible to weevil damage in both tests. The other remaining genotypes were intermediate types. This information is useful to improve grain protection in storage and varietal improvement/release program.